2018
DOI: 10.1167/iovs.17-23066
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable, Sustained-Released, Tacrolimus Microfilm Drug Delivery System for the Management of Allergic Conjunctivitis in a Mouse Model

Abstract: PURPOSE. To investigate the drug release profiles of a tacrolimus-loaded poly(D,L-lactide-co-ecaprolactone) (PLC) microfilm, and to evaluate its efficacy on the treatment of allergic conjunctivitis using a mouse model. METHODS.The in vitro and in vivo drug release profiles were first characterized. Balb/c mice were immunized with short ragweed (SRW) injection followed by re-challenges with topical SRW solution. The mice were divided into six groups (n ¼ 12 in each): negative control (NC); positive control (PC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…19 Several studies have shown that TAC plays an important role in the treatment of chronic allergic conjunctivitis, based on TAC's effect in substantially reducing the symptom score by approximately 50%. [20][21][22][23][24][25][26] In addition, the safety of long-term TAC application in the treatment of allergic conjunctivitis has also been verified. A study by Al-Amri et al, 27 using 0.1% topically applied TAC for treatment of AKC over 48 months, demonstrated the control and remission of the disease in the absence of other medications.…”
Section: Systematic Reviewmentioning
confidence: 92%
“…19 Several studies have shown that TAC plays an important role in the treatment of chronic allergic conjunctivitis, based on TAC's effect in substantially reducing the symptom score by approximately 50%. [20][21][22][23][24][25][26] In addition, the safety of long-term TAC application in the treatment of allergic conjunctivitis has also been verified. A study by Al-Amri et al, 27 using 0.1% topically applied TAC for treatment of AKC over 48 months, demonstrated the control and remission of the disease in the absence of other medications.…”
Section: Systematic Reviewmentioning
confidence: 92%
“…Immunomodulators, such as cyclosporin A and tacrolimus, suppress T-helper cell-mediated response, B-cell proliferation, and prostaglandin and cytokine release, especially interleukin (IL)-2, IL-4, and IL-5, which play roles in ocular allergic diseases [16]. It also blocks the release of histamine from mast cells.…”
Section: Topical Immunomodulatorsmentioning
confidence: 99%
“…Nanomedicine therefore becomes a potential alternative solution to deliver these drugs. As allergic conjunctival diseases are chronic and recurrent conditions, long-term use of topical eye drops and good patient compliance are necessary [16]. However, topical eye drops have a poor bioavailability of less than 10% and a short duration of action and therefore frequent application is required to achieve a therapeutic level [23,24].…”
Section: Topical Immunomodulatorsmentioning
confidence: 99%
“…All the quantification was performed on three randomly selected sections for each sample at 100× magnification by a single masked observer (ETWP). 23,24…”
Section: Histology and Immunohistochemistry (Ihc) Analysismentioning
confidence: 99%